Utilization of Oncotype DX in an Inner City Population: Race or Place?. (18th December 2013) - Guth, Amber A.; Fineberg, Susan; Fei, Kezhen; Franco, Rebeca; Bickell, Nina A.
Abstract : Oncotype DX, a 21-gene-array analysis, can guide chemotherapy treatment decisions for women with ER+ tumors. Of 225 ER+ women participating in a patient assistance trial, 23% underwent Oncotype DX testing: 31% of whites, 21% of blacks, and 14% of Hispanics (P = 0.04 ) were tested. Only 3 white women were treated at municipal hospitals and none was tested. 3% of women treated in municipal hospital as compared to 30% treated at tertiary referral centers were tested (P = 0.001 ). Within tertiary referral centers, there was no racial difference in testing: 32% of whites, 29% of blacks, and 19% of Hispanics (P = 0.25 ). Multivariate analysis (model c-statistic = 0.76; P < 0.0001 ) revealed that women who underwent testing were more likely to have stage 1B (RR = 1.70 ; 95% CI: 1.45–1.85) and to be treated after 2007 (RR = 1.34 ; 95% CI: 1.01–1.65) and less likely to be treated at a municipal hospital (RR = 0.20 ; 95% CI: 0.04–0.94). Women treated at municipal hospitals were less likely to undergo testing resulting in a misleading racial disparity that is driven by site of care. As Oncotype DX can reduce overuse of chemotherapy, it is imperative to expand testing to those who could benefit from yet experience underuse of this test, namely, women treated at safety net hospitals. This trial is registered with NCT00233077 .